Hijaiyah Matching Games Using Html5 - Pratami, Jauharoh; Yazid, Ahmad Subhan; Fatwanto, Agung (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
Hijaiyah letters are letters used in the writing of the Holy Qur'an. In learning hijaiyah letters, many children still have difficulties so alternative learning methods are needed to make children more interested in recognizing hijaiyah letters. Interactive hijaiyah learning using electronic media is also still rare. Of the several hijaiyah letter recognition applications which are available, it is also limited in the use of certain operating systems. This research uses the waterfall method. The technology used to build web-based games in this study is HTML5 because HTML5 has the advantage of the flexibility to run on various platforms through a browser. In addition, this application does not require an installation process like other applications, but simply by accessing the web page, the application can be used. The results of this study are Hijaiyah Match games that can be run on various operating systems through a browser. The test results show that this application can help children learn hijaiyah letters.